Analisis hubungan antara diet Mediterania dan Sindrom Koroner Akut: Pendekatan berbasis studi pustaka - Ulya, Firdausiyatul (Maliki Interdisciplinary Journal, 2024)
Acute Coronary Syndrome includes stable angina and myocard infarct is among the primary causes of death in world. Eating heabits is considered as important risk factor for ACS. The Mediterranean diet is a dietary approach focusing on low saturated fat intake and high consumption of plant-based oils. This study aims to analyze the association between the Mediterranean diet and the incidence of Acute Coronary Syndrome (ACS) through a literature review using the PubMed database by using PRISMA method. Five quantitative articles met the inclusion criteria, involving ACS patients with cross-sectional, cohort, and randomized controlled trial (RCT) study designs. The findings indicate that adherence to the Mediterranean diet is associated with a reduced risk of ACS. These results suggest that interventions to improve dietary habits, including the adoption of the Mediterranean diet, should be prioritized as a strategy for ACS prevention.